Clear cell sarcoma of soft tissue in an elderly male - Dayangku Norlida, Awang Ojep; Vernon Tan, S. Y.; Than Than, Aye; Mohamad Zulkarnaen, Ahmad Narihan (2025)
Introduction: Clear Cell Sarcoma of Soft Tissue (CCSST) is a rare, aggressive sarcoma with melanocytic differentiation, often termed “malignant melanoma of soft parts.” It primarily affects young adults aged 20–40 and commonly arises in tendons or aponeuroses of the extremities. Cases in older patients are uncommon, making diagnosis challenging. Case report: We describe a 68-year-old male who presented with a progressively enlarging, painless right thigh mass over five months, measuring 15x15 cm. He experienced weight loss and loss of appetite. MRI revealed an aggressive mass. Gross examination showed a poorly defined, greyish-tan tumour with areas of necrosis and haemorrhage. No obvious skin lesion was noted. Histologically, the tumour consisted of pleomorphic and spindle cells with vesicular nuclei, prominent nucleoli and focal melanin pigmentation. Immunohistochemistry was strongly positive for S100 and HMB45, with focal positivity for Melan A, supporting a diagnosis of CCSST. Surgical excision with clear margins was achieved. Discussion: CCSST primarily affects young adults, but occurrences in elderly patients are rare. The genetic hallmark, EWSR1-ATF1 fusion, remains consistent across age groups. Accurate diagnosis requires combining histology, immunohistochemistry, and molecular analysis. Surgical excision with clear margins remains the most effective treatment. However, systemic therapies offer limited benefit, especially in advanced cases. This case emphasises the need for considering CCSST in differential diagnoses across all age groups.